2020
DOI: 10.3390/ma13163537
|View full text |Cite
|
Sign up to set email alerts
|

High Quality Growth of Cobalt Doped GaN Nanowires with Enhanced Ferromagnetic and Optical Response

Abstract: Group III–V semiconductors with direct band gaps have become crucial for optoelectronic and microelectronic applications. Exploring these materials for spintronic applications is an important direction for many research groups. In this study, pure and cobalt doped GaN nanowires were grown on the Si substrate by the chemical vapor deposition (CVD) method. Sophisticated characterization techniques such as X-ray diffraction (XRD), Scanning Electron Microscope (SEM), Energy Dispersive X-Ray Spectroscopy (EDS), Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Since an experimental reports of T C reaching 200K in (Ga,Mn)As by patterning a heavily Mn-doped (Ga,Mn)As films into NWs [23], this success has inspired researchers to be interested in DMS NWs that takes advantage of the quantum size effect and surface effect of the NW. At the experimental level, the room temperature DMS NWs were developed using Mn-doped GaN NWs [24], Co-doped GaN NWs [25,26], Co-doped ZnO NWs [27], and (Cu,N)-codoped In 2 O 3 NWs [28]. Theoretically, Zhang et al suggested that the magnetic moment and the ferromagnetic states in (Ga,Mn)As NWs can be effectively regulated by the surface dangling bonds [29].…”
Section: Introductionmentioning
confidence: 99%
“…Since an experimental reports of T C reaching 200K in (Ga,Mn)As by patterning a heavily Mn-doped (Ga,Mn)As films into NWs [23], this success has inspired researchers to be interested in DMS NWs that takes advantage of the quantum size effect and surface effect of the NW. At the experimental level, the room temperature DMS NWs were developed using Mn-doped GaN NWs [24], Co-doped GaN NWs [25,26], Co-doped ZnO NWs [27], and (Cu,N)-codoped In 2 O 3 NWs [28]. Theoretically, Zhang et al suggested that the magnetic moment and the ferromagnetic states in (Ga,Mn)As NWs can be effectively regulated by the surface dangling bonds [29].…”
Section: Introductionmentioning
confidence: 99%
“…are a research focus in the scientific community due to their unique structures and integration of unusual physical properties. With unique advantages in the fields of electrics, optics, and magnetism, 1D nanomaterials hold immense promise in relevant nanotechnology applications [1][2][3][4][5][6][7][8][9][10]. Recently, nanostructured manganese silicides, including MnSi, Mn 5 Si 3 , Mn 3 Si, etc., received significant attention for their potential use in magnetic and spintronic applications [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%